2017
DOI: 10.1016/j.jot.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Local administration of Trolox, a vitamin E analog, reduced tendon adhesion in a chicken model of flexor digitorum profundus tendon injury

Abstract: SummaryBackgroundHand flexor tendon injuries are compromised with tendon adhesion. Tendon adhesion forms between flexor tendon and tendon sheath, reduces the range of motion of fingers, and affects their function. Oxidative stress is increased in flexor tendon after injury and might play a role in tendon adhesion formation. Trolox (6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid), a water-soluble analog of vitamin E, is antioxidative. Trolox reduced oxidative stress and the expression of fibrotic cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…More extensive extrinsic healing was observed in H 2 O 2 treatment groups, which resulted in less organized and aligned collagen fibers with peritendinous adhesion. It may help to explain why antioxidant supplementation can reduce tendon adhesion in flexor tendon injuries model . Apart from the sources of healing cells, origins of neovascularization were also better revealed at this sectioning plane.…”
Section: Discussionmentioning
confidence: 86%
“…More extensive extrinsic healing was observed in H 2 O 2 treatment groups, which resulted in less organized and aligned collagen fibers with peritendinous adhesion. It may help to explain why antioxidant supplementation can reduce tendon adhesion in flexor tendon injuries model . Apart from the sources of healing cells, origins of neovascularization were also better revealed at this sectioning plane.…”
Section: Discussionmentioning
confidence: 86%
“…[ 28 ] In another study, local vitamin E analogue was shown to reduce postoperative adhesion by antioxidant and antifibrotic effects in an experimental chicken model with flexor digitorum profundus tendon injury. [ 12 ] Reduced postoperative adhesion was shown in another study where collagen-elastin matrix was used to prevent postoperative adhesion in an experimental rabbit model undergoing flexor tendon repair. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…When experimental studies on flexor digitorum profundus tendon adhesion are examined, it is seen that chicken models are frequently used as subjects. [12,13] We preferred to use chickens for reasons such as low cost and the adequate accommodation conditions in the animal laboratory where we carried out the study. Therefore, in this study, we aimed to biomechanically and histopathologically investigate the effects of MB on preventing postoperative adhesion in chickens undergoing full-thickness flexor tendon incision.…”
mentioning
confidence: 99%
“…Many methods have been used to prevent tendon adhesion, such as the improvement of surgical technology, the use of barriers, systemic or local application of drugs and chemicals. Although these methods can reduce adhesions to some extent, the residual or recurrent adhesions still need to be resolved [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%